2014
DOI: 10.1103/physrevc.89.054601
|View full text |Cite
|
Sign up to set email alerts
|

Extended Glauber model of antiproton-nucleus annihilation for all energies and mass numbers

Abstract: Previous analytical formulas in the Glauber model for high-energy nucleus-nucleus collisions developed by Wong are utilized and extended to study antiproton-nucleus annihilations for both high and low energies, after taking into account the effects of Coulomb and nuclear interactions, and the change of the antiproton momentum inside a nucleus. The extended analytical formulas capture the main features of the experimental antiproton-nucleus annihilation cross sections for all energies and mass numbers. At high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…3(c) shows a plot of σ BI ann (L) given by Eq. (12). As expected, the L = 0 curve faithfully follows the 1/p dependence which seems to imply the difference…”
Section: Semiclassical Analyses Of the Annihilation Oscillations And ...supporting
confidence: 81%
See 1 more Smart Citation
“…3(c) shows a plot of σ BI ann (L) given by Eq. (12). As expected, the L = 0 curve faithfully follows the 1/p dependence which seems to imply the difference…”
Section: Semiclassical Analyses Of the Annihilation Oscillations And ...supporting
confidence: 81%
“…To unravel this mystery, there has been a great deal of experimental and theoretical investigations on matter-antimatter interactions. So far, most of the obtained information centers around antiproton-nucleus (pA) reactions and structures [2][3][4][5][6][7][8][9][10][11][12][13][14]. The corresponding information on antineutron-nucleus (nA) reaction [15], on the other hand, remains comparatively sparse and limited with the most recent work from the OBELIX's collaboration [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these competing effects, optimal correlated two-particles motion occurs at an intermediate coupling strength [15]. It has been previously reported that such competition also leads to a nonmonotonic behavior of the BO amplitude [17] and Anderson localization [34,35].…”
mentioning
confidence: 99%
“…From Eq. (20) with b(t) = 1 we have ω(t) = 1 while recall that m(t) = 1, thus M (z) = Ω(z) = 1 and from (7), (8) we find a 0 (z) = 1, a 2 (z) = 0. From Eq.…”
Section: Engineering the Lattice Output Using Shortcuts To Adiabmentioning
confidence: 92%
“…Many recent studies have demonstrated that a family of photonic lattices, implemented in arrays of evenescently coupled waveguides [1], provides the ideal testbed for a large variety of quantum phenomena [2]. We mention the observation in these lattices of Bloch-like revivals [3][4][5], Anderson localization of light [6][7][8], and the classical analog of coherent states and quantum correlations [9,10], to name a few. On the other hand, ideas from quantum mechanics have inspired the design of optical structures with desired properties.…”
Section: Introductionmentioning
confidence: 99%